IMAGE-BASED SEXUAL ABUSE AND THE REQUIREMENT OF MOTIVE UNDER THE FILMS AND PUBLICATIONS AMENDMENT ACT: A CRITICAL ASSESSMENT - Blake Martin (Obiter, 2024)
Section 18F(1) of the Films and Publications Amendment Act (FAPAA) prohibits the commission of image-based sexual abuse (IBSA). This contribution critically assesses the requirement “with the intention of causing that individual harm” contained in section 18F(1)(b) of the FAPAA. It is demonstrated that the requirement “with the intention of causing that individual harm” cannot be understood as indicating intention in the legal sense (that is, dolus). Rather, section 18F(1)(b) refers to motive, or the reason for the perpetrator’s conduct. Section 18F(1)(b) should thus more accurately read (to avoid confusion with dolus) “with the ‘motive’ of causing that individual harm”. In the determination of criminal liability, motive has been repeatedly affirmed as irrelevant. The author supports this conclusion. In addition, the underlying reasons motivating the perpetration of IBSA vary substantially. Thus, requiring proof of motive in this respect is ill considered.However, motive is relevant to the process of sentencing. Some motives for the perpetration of IBSA may be considered by the sentencing court as “aggravating”, and, accordingly, attract a harsher sentence. Section 56A(2)(a) of the Criminal Law (Sexual Offences and Related Matters) Amendment Act indicates several motives (for the commission of sexual offences) that might be considered “aggravating”. These include where a sexual offence is committed with the motive “to gain financially, or receive any favour, benefit, reward, compensation or any other advantage”. Many of these motives are witnessable in cases of IBSA, and being a sexual offence that should be located in the Criminal Law (Sexual Offences and Related Matters) Amendment Act, should (in terms of section 56A(2)(a)) be considered “aggravating”. It is also shown that other aggravating motives listed in 56A(2)(a), such as to receive any “benefit” or “reward”, may apply when IBSA is committed for purposes of revenge.